A home made Z-scan set up for the nonlinear optical investigations in solids. (2015) - Dayal, Sardul Singh; Joseph, David
An indigenous Z-scan set up has been fabricated for the study of nonlinear optical properties of solids. Few crystals have been used to verify the performance of the home made system. An automatic scanning is made possible by burning a program to the IC. Although the paper is based on instrumentation, it also summarises for Z-scan set ups commonly used in nonlinear optical studies and their relative advantages. A solid (ruby crystal) and CS2 liquid has been used for parametric studies.